Search for massive resonances in dijet systems containing jets tagged as W or Z boson decays in pp collisions at √s=8 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjan, C.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; Hartl, C.; et al. (SPRINGER, 2014)
A search is reported for massive resonances decaying into a quark and a vector boson (W or Z), or two vector bosons (WW, WZ, or ZZ). The analysis is performed on an inclusive sample of multijet events corresponding to an integrated luminosity of 19.7 fb(-1), collected in proton-proton collisions at a centre-of-mass energy of 8 TeV with the CMS detector at the LHC. The search uses novel jet-substructure identification techniques that provide sensitivity to the presence of highly boosted vector bosons decaying into a pair of quarks. Exclusion limits are set at a confidence level of 95% on the production of: (i) excited quark resonances q* decaying to qW and qZ for masses less than 3.2 TeV and 2.9 TeV, respectively, (ii) a Randall-Sundrum graviton G(RS) decaying into WW for masses below 1.2 TeV, and (iii) a heavy partner of the W boson W' decaying into WZ for masses less than 1.7 TeV. For the first time mass limits are set on W' -> WZ and G(RS) -> WW in the all-jets final state. The mass limits on q* -> qW, q* -> qZ, W' -> WZ, G(RS) -> WW are the most stringent to date. A model with a bulk graviton G(bulk) that decays into WW or ZZ bosons is also studied.
Keywords: Jet substructure; Jets; Jet physics; Hadron-Hadron Scattering; Particle and resonance production; Physics